Valens and the Goths: a Constantinian model? - Benedetti, Pedro (Romanitas - Revista de Estudos Grecolatinos, 2026)
The Goths’ support for Procopius’ usurpation against Valens in the eastern regions of the Roman Empire in 365 brought about a new phase in the Romano-Gothic relations. Committed to subduing them for having challenged his authority, Valens devoted the next four years to campaigns in the Danube region, which did not yield good results. In this article, I will discuss to what extent Valens’ dealings with the Goths were anchored in the precedents established by Constantine and what innovations were brought by Valens upon this model.